Semiotics of the ‘A Woman in A Pink Hijab’ photo on Harian Kompas’ Instagram - Muhammad Rhomy Dellan; Bramedia Ridho Satria; Satria Sofyan Pramadia (Privietlab, 2026)
Instagram is now a highly graphic platform in terms of news flow and can turn a photojournalistic image into a digital icon. This study analyzes a photo series of a woman in a pink hijab that was posted by Harian Kompas on August 28, 2025, during a demonstration in front of the Indonesian House of Representatives (DPR RI). This study poses the question of how visual displays–the pink hijab, riot shields, the Indonesian flag, and bodily gestures–produce meaning regarding gender, civic identity, and symbolic resistance. It employs a descriptive qualitative research design to apply Barthesian signification orders (denotation, connotation, myth) to four photographs in a single carousel post and triangulate the discourse of the mainstream news regarding the concept of ‘pink brave’. The analysis finds that denotatively, the images document a civilian–police confrontation. Connotatively, color contrast and barricade composition foreground an opposition between 'ordinary people' and state power while renegotiating stereotypical femininity into moral courage. At the mythic level, the mother emerges as a symbol of civic motherhood that defines resistance as a form of patriotism when the flag is raised during war. This research discovered that Instagram photojournalism does not merely report on situations but integrates sense into symbols that can be exchanged on the digital open platform.